Preference and Utilization of Media Channels as Communication Instruments of Local Public Administrators in Bacolod City, Negros Occidental - Pascual-Dormido, Yasmin (International Journal of Scientific Research and Management (IJSRM), 2023)
This descriptive study sought to determine the level of preference and extent of utilization of local public administrators (LPAs) of Bacolod City of media channels as communication instruments. Needed data were collected from all 85 middle-level managers holding positions as department head, assistant department head, division chief, and assistant division chiefs in the local government unit (LGU)  using a survey questionnaire that has passed both validity and reliability test. Subsequent analyses reveal respondents' level preference and extent of utilization of social media, specifically Facebook and mainstream media (television/radio and newspapers) as information soures and feedback instruments   concerning their functions as public administrators. Respondents exhibited a "high level" of preference and a "great extent" of utilization in the above-mentioned areas. Meanwhile, a significant difference was present in demographic variables like age and length of service. There was a significant relationship between the LPA’s level of preference and extent of utilization. It has been established that respondents' preference led to their utilization of a specific medium. These findings call for a review and possible modification of departments’ and divisions' communication strategies for relevance, transparency, and responsiveness.